BAYANG DI BALIK TIANG: REINTERPRETASI ATAS NOVEL SITI NURBAYA KARYA MARAH ROESLI - Rusel Akbar Fauzi; Sahrul Sahrul; Nurhaida Nuri (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT             Theater of Bayang di Balik Tiang (Shadow behind the Pole) is a reinterpretation of novel Siti Nurbaya by Marah Roesli. This novel tells a miserable romance between Siti Nurbaya and Samsul Bahri. This story was started with these lovers’ relationship that’s ultimately blocked by the proposal of a panghulu kaum (headman) in Minangkabau named Datuk Maringgih. Siti Nurbaya, who never wishes to be Datuk Maringgih’s wife, eventually had to accept the proposal due to the debts her father owed to Datuk Maringgih. Siti Nurbaya accepted Datuk Maringgih’s Proposal because she was the only who could save her family’s economy, which underwent a bankruptcy.The creation of Bayang di Balik Tiang theater was started with the play arrangement. The fundamental difference between Siti Nurbaya and this play was the presence of mamak (mother’s brothers) character in this work, who could be deemed guilty of Siti Nurbaya’s miserable fate. The creator of this work also provided objective nationhood senses by reinterpreting characters in the roman like Datuk Maringgih, Samsul Bahri, Siti Nurbaya, and the emergence of new characters besides Mamak Angku Palo, namely Hanafi as Samsul Bahri’s friend. Those characters functioned as “dialectical space” in understanding the meaning of love, either love between opposite sexes or love towards one another or love towards the homeland. This play was arranged in montage way namely a narrative storyline using fast-and-mobile-ordered scenes. The space and the time wee created in a random and leaping order. The plot arranged was not linear. Keywords: Theater, Siti Nurbaya Novel, Mamak, Montage